Electrochemical synthesis of thin HKUST-1 layers on copper mesh - Van Assche, Tom R.C.; Desmet, Gert; Ameloot, Rob; De Vos, Dirk E.; Terryn, Herman; Denayer, Joeri F.M. (Microporous and mesoporous materials, 2012)
[Display omitted] ► HKUST-1 metal organic framework layers were grown on a porous support. ► Control over electrochemical synthesis parameters is needed to avoid structural damage. ► Crystal size strongly depends on water content of synthesis mixture. Metal-organic framework HKUST-1 was synthesized on a porous copper mesh using an electrochemical synthesis technique. By partially oxidizing the mesh in a controllable manner, thin crystal layers could be synthesized without structurally damaging the supporting mesh. Good control over the crystal size could be obtained by varying the water content of the synthesis mixture. This technique allows the formation of crystal layers overgrowing the porous copper support at mild temperatures and short synthesis times.